Genetic polymorphisms in human telomerase reverse transcriptase (hTERT) gene polymorphisms do not associated with breast cancer in patients in a turkish population: hospital-based case-control study - Aydin, Muhsin; Sümbül, Ahmet Taner; Camuz Hilaloğullari, Günay; Bayram, Süleyman (Cellular and Molecular Biology, 2018)
Breast cancer (BC) is encountered most frequently in developed or developing countries. It is the most common cancer in humans following lung cancer, and it is the most common cancer type resulting in mortality in women. Genetic polymorphisms are among the genetic factors that play an important role in the development of the breast cancer. The purpose of this study was to investigate the effect of five functional single nucleotide polymorphisms (SNPs) of hTERT (rs2736109 G>A, rs2735940 T>C, rs2853669 A>G, rs2736098 G>A, and rs2736100 T>G) on susceptibility to BC in Turkish population. The genotype frequency of hTERT rs2736109 G>A, rs2735940 T>C, rs2853669 A>G, rs2736098 G>A, and rs2736100 T>G polymorphisms were determined by using a polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) and TaqMan methods in 123 subjects with GC and 122 healthy control subjects. The mean age value of the BC patients was 51.58±11.28 (among them 8 subjects â‰¤35 and 115 subjects >35). In this study, it was found that there was no statistical difference between hTERT rs2736109 G>A, rs2735940 T>C, rs2853669 A>G, rs2736098 G>A, and rs2736100 T>G polymorphisms that can be associated with risk of BC.